Una sentenza storica - Fiori Nastro, Paolo; Fagioli, Luca (Il sogno della farfalla, 2018)
In a sentence published last April, in relation to a case of “abuse of the profession of psychotherapist”, the Italian Supreme Court (Corte di Cassazione) has gone to some length to lay down some principles, that, given the authoritative nature of this body, can be considered the founding principles of the psychotherapeutic profession. The sentence stresses the fact that psychoanalysis is not a free intellectual activity but a psychotherapy like all the others and distinguishes itself on the basis of the methods it uses, and as such, psychoanalystsmust respect law 56/89 which sets the rules for psychotherapies. Furthermore the Supreme Court highlights the fact that “talking” constitutes a real and proper therapy for real and proper diseases, and so, psychotherapy is a typical activity of the medical profession. Ultimately this sentence, in contrast to what is commonly held in the scientific world, indicates that the Supreme Court is of the idea that psychotherapy is a therapy which offers a cure for real and proper diseases, which cannot have an organic basis if they can be cured by “talking”.